The double-edged nature of nicotine: toxicities and therapeutic potentials - Cao, Yun; Sun, Jiali; Wang, Xiaofeng; Zhang, Xiaoyu; Tian, Huijuan; Huang, Lingling; Huang, Ze; Zhang, Yaping; Zhang, Jin; Li, Lin; Zhou, Shun (Frontiers in Pharmacology, 2024)
Nicotine is the primary addictive component of cigarette smoke and is associated with various smoking-related diseases. However, recent research has revealed its broader cognitive-enhancing and anti-inflammatory properties, suggesting its potential therapeutic applications in several conditions. This review aims to examine the double-edged nature of nicotine, encompassing its positive and negative effects. We provide a concise overview of the physiochemical properties and pharmacology of nicotine, including insights into nicotine receptors. Therefore, the article is divided into two main sections: toxicity and therapeutic potential. We comprehensively explored nicotine-related diseases, focusing on specific signaling pathways and the underlying mechanisms that contribute to its effects. Furthermore, we addressed the current research challenges and future development perspectives. This review aims to inspire future researchers to explore the full medical potential of nicotine, which holds significant promise for the clinical management of specific diseases.